Home Branding - redefining hospitality as part of responsible tourism - Devaki R Menon
As tourism is becoming the prime contributor to the growth of the economy, the government is taking efforts to promote tourism and provide tourists the best in hospitality services. The Kerala Tourism Development Cooperation has started taking initiatives towards the realization of responsible tourism in Kerala in the case of ayurveda, houseboats and home-stays. The article focuses on the concept of home-stay, the package, price, place and promotion aspects which will give an experiential vacation to the travellers. It describes on how the initiatives taken by Kerala Tourism becomes worthwhile for the visitors as well as for the people of Kerala.